Evaluation of the effects of various additives on the acceptability of kilishi (2003)
The semitendinosus muscle of hot de-boned beef was trimmed of all visible fats, bones and connective tissue. The cleaned muscle was weighed and sliced into thin sheet of 0.17-0.20cm thick and between 60-80cm long. The sliced meat was infused with locally available spice, condiments and other materials such as salt, sugar, maggi seasoning, peanut paste and water. The local spices and condiments used include; onion, alligator pepper, cloves, chillies, ginger, 'gyadar miya’ (Hausa name), black pepper and spice mixture containing locust bean, groundnut powder and other seasoning. The experiment comprised of six(6) treatments. Treatment one (Tl), served as the control with all ingredients present while ginger, alligator pepper cloves, gyadamiya and black pepper were absent in T2 T3 T4 Ts and T6 respectively. The result of the taste panelist showed that in terms of flavour, the Kilishi where alligator pepper was absent was most preferred. The result also showed that one or two of the spices could replace each other without any marked deference in flavour, juiciness, pungency, tenderness and overall acceptability.